Clinical impact of positron emission tomography or positron emission tomography/computed tomography in the posttherapy surveillance of endometrial carcinoma: evaluation of 88 patients. Issue 6 (1st October 2008) - Park, J.-Y.; Kim, E. N.; Kim, D.-Y.; Kim, J.-H.; Kim, Y.-M.; Kim, Y.-T.; Nam, J.-H.
Abstract : The objective of this study was to evaluate the validity and clinical impact of positron emission tomography (PET) or positron emission tomography/computed tomography (PET/CT) using 18-fluoro-2-deoxy-D-glucose in the posttherapy surveillance of patients with endometrial carcinoma. Eighty-eight patients previously treated for histopathologically diagnosed endometrial adenocarcinoma underwent 99 PET or PET/CT scans at follow-up visits at Asan Medical Center, Seoul, Korea, between 2001 and 2007. The standard of reference for tumor recurrence consisted of histopathologic confirmation or follow-up information at least 6 months after PET or PET/CT. Of the 88 patients, 24 underwent PET ( n = 11) and/or PET/CT ( n = 14) scans due to suspected disease recurrence. The sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of PET and/or PET/CT in detecting recurrence in these patients were 100%, 83.3%, 96%, 95%, and 100%, respectively. Especially, PET/CT revealed true-positive findings in three patients with elevated tumor markers but negative CT findings. The remaining 64 patients underwent PET ( n = 8) and/or PET/CT ( n = 66) as part of routine posttherapy surveillance; these patients were asymptomatic, with no evidence of disease. The sensitivity, specificity, accuracy, PPV, and NPV of PET and/or PET/CT in detecting recurrence in these patients were all 100%. Clinical decisions on treatment were changed in 14 (21.9%) patients by introducing PET or PET/CT into their conventional posttherapy surveillance program. PET and/or PET/CT were highly effective in discriminating true recurrence in patients with suspected recurrence, highly sensitive in detecting recurrence in asymptomatic patients, and had impacts on clinical decisions in a considerable portion of patients.